Highly Selective and Sensitive Detection of Fe3+ by 1,8-Naphthalimide-Based Fluorescent Sensors - Wang, Shuping; Xu, Dongmei (Asian Journal of Chemistry, 2013)
Highly selective and sensitive detection of Fe3+ by two 1,8-naphthalimide-based fluorescent sensors, 2-(2-(dimethylamino)ethyl)-6-((2-(dimethylamino)ethyl)-amino)-1H-benzo[ de]isoquinoline-1,3(2H)-dione (MMN) and 2-(2-(diethylamino)ethyl)-6-((2-(diethylamino)-ethyl)amino)-1H-benzo[de]isoquinoline-1,3(2H)-dione (EEN) in N,N-dimethyl formamide is reported. The fluorescence intensity of MMN and EEN is greatly enhanced by Fe3+ ion with the response time of less than 1s. The maximum fluorescence intensity of the sensors is linearly dependent on the concentration of Fe3+ within the range of 10-100 μM. The binding stoichiometry indicates that a 2:1 complex is formed between Fe3+ and the sensor and the detection limits for MMN and EEN are 180 and 310 nM, respectively. A large number of biologically relevant ions show no obvious interferences with the detection.